Effects of heat: UK exercise Saif Sareea 3 and interpreting military climatic guidance. Issue 6 (19th May 2020) - White, Samuel; Smith, M B
Abstract : Introduction: Over recent years much research, both civilian and military, has occurred in the field of heat illness. This has helped force health protection and medical management of service personnel operating in hot climates. Exercise Saif Sareea 3 in Oman saw a collection of presentations to the deployed UK medical treatment facilities due to the effects of heat. Method: This paper aims to describe the case series of 24 casualties that presented to the deployed primary care facilities and 17 that were admitted to the deployed secondary care facility due to the effects of heat. Results: Only 10 casualties fulfilled the in-theatre diagnostic criteria for heat illness, of which two were of moderate severity and required aeromedical evacuation to the UK. Conclusions: Commanders appeared extremely well read on Joint Service Publication 539 (JSP539; May 2017) Heat Illness and Cold Injury: Prevention and Management, following the Brecon enquiry, and were proactive in managing their force in preventative measures. This likely contributed towards the low numbers of patients with heat illness seen on the exercise. JSP539 did, however, appear to have some limitations when trying to apply it to all patients seen within the operational patient care pathway, and some areas for development are discussed.